Interrelations of knowledge management for university education: a bibliographic review - de Almeida, Arielle Lopes [UNESP]; Damian, Ieda Pelógia Martins [UNESP] (Universidad Nacional de La Plata, 2023)
The university, through education, aims to promote the autonomy of its students in the construction of knowledge. By conceiving it in a continuous flow of meanings and redefinitions of knowledge in the university, contributions of knowledge management are identified as a facilitator for this construction and also for sharing. Thus, in order to understand how academic research has contributed to the subject of knowledge management for teaching-learning in university education, this article aims to identify the interrelationships between knowledge management processes and university education, through a bibliographic literature review. As a result, the interdisciplinarity between some theories of knowledge management and education is highlighted and the main axes addressed in this study are presented.
Interrelaciones de la gestión del conocimiento para la educación universitaria: una revisión bibliográfica
Interrelações revisão bibliográfica da gestão do conhecimento para a educação universitária: uma revisão bibliográfica
Keywords: Bibliographic review; Organizational learning; Teaching-learning; University education